Portable height-adjustable constructional engineering intelligent information acquisition device - CHI QINGJUAN; LI ZUNQIANG (2022)
The utility model discloses a portable height-adjustable constructional engineering intelligent information acquisition device which comprises a bottom plate, the upper surface of the bottom plate is fixedly connected with a fixed plate, the interior of the fixed plate is slidably connected with a lower sliding rod, and the upper surface of the lower sliding rod is fixedly connected with two lower active adjusting rods. The inner side of the lower driving adjusting rod is rotationally connected with a lower driven adjusting rod, the lower end of the lower driven adjusting rod is rotationally connected with the interior of the fixing plate, the upper end of the lower driving adjusting rod is rotationally connected with an upper driving adjusting rod, and the upper end of the lower driven adjusting rod is rotationally connected with an upper driven adjusting rod; the upper end of the upper driven adjusting rod is fixedly connected with an upper sliding rod, the lower driven adjusting rod can be driven to move t